Public pensions, changing employment patterns, and the impact of pension reforms across birth cohorts - a microsimulation analysis for Germany - Johannes Geyer; Viktor Steiner (Verein für Socialpolitik, 2010)
We analyze the impact of changing employment patterns and pension reforms on the future level of public pensions across birth cohorts in Germany. The analysis is based on a microsimulation model which accounts for cohort effects in individual employment and unemployment and earnings over the lifecycle as well as the differential impact of recent pension reforms on birth cohorts. Cohort effects estimated on the German Socio-Economic Panel (SOEP) for for individuals born between 1937 and 1971 vary greatly by region, gender and education and strongly affect lifecycle wage profiles, in particular in East Germany and for people with little education. Using simulated life cycle employment and income profiles, we project gross future pensions across cohorts taking into account changing demographics and recent pension reforms. Simulations show that pension levels for East German men and women will fall dramatically among younger birth cohorts, not only because of policy reforms but due to higher cumulated unemployment. For West German men, the small reduction of average pension levels among younger birth cohorts is mainly driven by the impact of pension reforms, while future pension levels of West German women are increasing or stable due to rising labor market participation of younger birth cohorts.
Keywords: H55; J26; J11; 330; Public pensions; cohort effects; microsimulation